High-intensive physical rehabilitation approach in children and adolescents with acquired brain injury during subacute phase (REHABILITY): a feasibility study protocol - Jan Willem Gorter; Christiaan Gmelig Meyling; Olaf Verschuren; Ingrid Rentinck; Irene van der Steen; Raoul Engelbert (BMJ Open)
Introduction While principles of neuroplasticity and motor learning emphasise the potential of high dosage of physical rehabilitation in children and adolescents with acquired brain injury (ABI) during the subacute phase, we lack empirical evidence to demonstrate its impact in terms of meaningful outcomes. Clinical research is needed to investigate adequate dosage of physical rehabilitation and its effects on outcomes with reliable and validated outcome measurements. In this study we will investigate the feasibility of a highly intensive physical rehabilitation intervention and outcomes with reliable and valid outcome measurements.Methods and analysis Our study with a prospective case-series design will evaluate (1) The safety and feasibility of a high-intensive physical rehabilitation programme to improve functioning and participation in children and adolescents with ABI, and (2) The feasibility of a core set of clinical outcome measures to assess recovery on relevant International Classification of Functioning, Disability, and Health domains during the subacute phase. We aim to include 10–15 children and adolescents aged 6–20 years with moderate-severe ABI during subacute rehabilitation in a specialised youth department for inpatient rehabilitation in The Netherlands. In the rehabilitation programme, we aim at a highly intensive approach of 3–5 hours physical rehabilitation per day during inpatient rehabilitation. Frequent and systematic assessment (baseline, each consecutive 6 weeks -if applicable- and at discharge) through a core set of outcome measures will provide insights into the degree of recovery of motor and cognitive functioning. We use descriptive and inferential statistics and thematic content analysis for analysis of the data.Ethics and dissemination The study has been approved by the Medical Ethics Research Committee of the University Medical Hospital, Utrecht (reference number: 23U-0628). We aim to disseminate our findings in peer-reviewed journals and present at national and international conferences.